Development and validation of an interdisciplinary manual for use of parents, teachers and health professionals in the education of children with chronic illness - Licuan, Ma. Cecilia D. (2007)
This is a three-phased descriptive and quasi-experimental study with an ultimate goal of developing an interdisciplinary Teaching Manual that can be used by parents, teachers and health professionals to promote therapeutic healing of children with chronic illness (CWCI) through enjoyable education with incidental cognitive and psychomotor benefits. Four research questionnaires were developed and given to four groups of respondents comprising of 80 CWCI, 80 parents of CWCI, 14 teachers and 28 health professionals handling CWCI. The manual developed was validated by 10 experts belonging to the field of SPED, pediatric health care, rehabilitation medicine, educational psychology, research and administration. It was proven effective in improving psychosocial scores in both intrapersonal and interpersonal psychosocial characteristics.